Characterization of resistance-welded thermoplastic composite double-lap joints under static and fatigue loading. (June 2015) - Dubé, Martine; Chazerain, Aurélie; Hubert, Pascal; Yousefpour, Ali; Bersee, Harald EN
An experimental investigation of resistance welding of thermoplastic composite double lap shear (DLS) joints is presented. DLS specimens consisting of unidirectional carbon fibre/polyetheretherketone (CF/PEEK), carbon fibre/polyetherketoneketone (CF/PEKK), carbon fibre/polyetherimide (CF/PEI) and 8-harness satin weave fabric glass fibre/polyetherimide (GF/PEI) composites were resistance welded using a stainless steel mesh heating element. The welded specimens were tested under static and fatigue loadings, and the quality of the welds was examined using optical and scanning electron microscopy. Weld strengths of 53, 49, 45 and 34 MPa were obtained for CF/PEEK, CF/PEKK, CF/PEI and GF/PEI DLS joints, respectively. Indefinite fatigue lives were obtained between 20 and 30% of the ultimate static failure loads of the joints. Performances of the resistance-welded DLS and single lap shear (SLS) joints were compared. It was shown that the effect of joint geometry, that is, DLS versus SLS, on the mechanical performance of the resistance-welded joints is minimal, indicating a good resistance of welded joints to peel stresses.